COST AND QUALITY OF LIFE IN PATIENTS UNDERWENT HIP ARTHROPLASTY IN A BRAZILIAN HOSPITAL - Maria-Roxana Viamont-Guerra; Alex Takao Sasai; Júlia Martins Rodrigues; Rodrigo Guimarães; Eliane Antonioli; Mario Lenza (Acta Ortopédica Brasileira)
ABSTRACT Introduction: There are few studies in Brazil evaluating the quality of life and costs of patients undergoing total hip arthroplasty (THA). Purpose: (1) To describe the total cost, quality of life and functional scores of patients undergoing THA in a Brazilian private hospital; (2) to determine preoperative factors associated with quality of life and total cost; and (3) to evaluate the association between cost and quality of life. Methods: Of the 1061 patients included, pre- and peri-operative data, total costs, pre- and post-operative functional scores (HOOS, WOMAC) and quality of life scores (EQ-5D) were collected over 2 years. Results: EQ-5D, HOOS and WOMAC improved from 0.492, 54.5 and 45.2, respectively, to 0.888, 90 and 5.9 at 1-year follow-up, and 0.892, 90.4 and 4.0 at 2-year follow-up. The average cost was R$43,324.22±11,323. Associations were observed between EQ-5D variation and male sex (RM=1.058; p=0.03) as well as age (RM=0.996; p<0.001). No association was found between total cost and EQ-5D. Conclusions: The average cost of patients undergoing THA was R$43,324.22. There was an improvement in quality of life and function, an association between quality of life and male sex and age, however no association was found between total cost and quality of life. Level of evidence IV; Case Series.